Collaborative marketing innovation: How to energize social capital to enhance MSME’s performance? - Muna, Nalal; Sukresna, I Made; Praswati, Aflit Nuryulia (Asian Management and Business Review, 2024)
An entrepreneurial network is one of the most prominent strategic resources for business. Even though micro, small, and medium-sized enterprises (MSMEs) face several challenges arising from their liability of smallness, they can leverage the advantages of having strong network ties. This study aims to examine how social capital derived from entrepreneurial networks (both formal and informal) can encourage collaborative marketing innovation and speed-to-market to enhance marketing performance. A total of 161 MSME owners from various industries participated in a field survey that was conducted using self-administered questionnaires. Data is analyzed using Structural Equation Modelling with AMOS software. The Resource Advantage Theory of Competition (RAToC) emphasizes the dynamic nature of competition in provoking disequilibrium through collaboration with other organizations. The result shows that collaboration helps companies in integrating resources in the marketing innovation process such as obtaining input for product development and supporting product promotion. The study also indicates that collaborative marketing innovation has become the most salient variable that accelerates time-to-market and enhances MSME performance.